The role and function of a sports event organiser - Praznik, Timotej (Varstvoslovje, 2020)
Purpose: The purpose of the paper is to examine the organisation of a sports event - more precisely, a football match, specifically from the point of view of safety. We compared the Slovenian practice of event organising with how sports events are organised in Serbia and Austria. Design/Methods/Approach: First we conducted a literature and normative bases review. The research was conducted through interviews with spokespersons from the football clubs - NK Celje, FK Partizan and SK Sturm Graz. We conducted a telephone interview with the security manager of the European Football Association and also included our own observations from attending the Serbian championship match. Findings: Our research shows that despite the existence of subnational legislation, there are differences in understanding of ensuring safety at sporting events in the analysed countries. As the most common factors that can affect safety and security at a sports event we identified the following: personnel, supporter groups, pyrotechnics and infrastructure. Research Limitations/Implications: Our research is limited to three countries and to three football clubs that were willing to take part in our research. Originality/Value: Research findings are based on the perspective and experience of football club security managers, presenting main risk factors and corresponding measures for ensuring safety and security at football matches.
Keywords: nogometna tekma; safety; security measures; security risks; sport event; športna prireditev; varnost; varnostna tveganja; varnostni ukrepi